2011
DOI: 10.1007/s11356-011-0552-y
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and diversity of Sphingomonas in Shenfu petroleum-wastewater irrigation zone, China

Abstract: The newly designed Sphingomonas-selective primers were specific and practicable for analyzing Sphingomonas abundance and diversity in petroleum-contaminated soils. The significant correlation between the abundance and the ratios of PAHs to TPH suggested an important role of Sphingomonas in PAH bioremediation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
(49 reference statements)
4
9
0
Order By: Relevance
“…A 70-km irrigation channel was constructed in 1960's, and the wastewater mainly comes from an oil refinery. After 50-year exposure to petroleum-containing wastewater, soils in the irrigation zone have been seriously contaminated (Li et al, 2005 ; Zhou et al, 2012 ). Plasmid pSFA231 was isolated from a sediment sample collected from down-stream of the irrigation channel.…”
Section: Methodsmentioning
confidence: 99%
“…A 70-km irrigation channel was constructed in 1960's, and the wastewater mainly comes from an oil refinery. After 50-year exposure to petroleum-containing wastewater, soils in the irrigation zone have been seriously contaminated (Li et al, 2005 ; Zhou et al, 2012 ). Plasmid pSFA231 was isolated from a sediment sample collected from down-stream of the irrigation channel.…”
Section: Methodsmentioning
confidence: 99%
“…Water is used in daily activities, which in turn increases the need for efficient wastewater treatment facilities. Due to rapid industrialization, a large quantity of polluted water is generated every year by different industries such as textile (Zheng et al 2012), leather (Natarajan et al 2013), pharmaceutical (Farhadi et al 2012;Boroski et al 2009), heavy metal (Al Aji et al 2012), cadmium removal (Bayar et al 2013;Yilmaz et al 2012), arsenic (Can et al 2012(Can et al , 2014, dairy processing (Idris et al 2012), paint (Singh et al 2015), petroleum (Zhou et al 2012), pulp and paper (Bengtsson et al 2008;Pokhrel and Viraraghavan 2004), distillery (Lucas et al 2009), fertilizer (Srivastava et al 1996), tannery (Houshyar et al 2012), landfill (Wu et al 2011), bakers yeast (Gengec et al 2012), food processing (Pocostales et al 2012), biodiesel (Ngamlerdpokin et al 2011) and olive packaging industries (García-García et al 2011;Kul et al 2015), Pistachio processing industry Fil et al 2014), etc. The pulp and paper industry is a large consumer of fresh water and an important source of wastewater (Ashrafi et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous real-time PCR analysis indicated that all 15 petroleum-contaminated soil samples gave positive signals for Sphingomonas . 11 However, in this study only 12 soils yielded yellow colonies on the selective LB plates with Sm. The number of yellow CFUs ranged from 0.6 × 10 3 to 1.6 × 10 5 CFUs g −1 soil ( Table 1 ).…”
Section: Resultsmentioning
confidence: 51%
“…The physicochemical soil characteristics and the PAH concentrations in the soil were reported in our previous study. 11 Typically, soil samples collected from the up- and mid-stream sites accumulated more petroleum contaminants compared with those from the down-stream sites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation